Humanisation of Care in Intensive Care Units: A Systematic Review of the Literature - VIRISSIMO; VIVEIROS; ALVES; GONÇALVES; SOUSA (The Bioscan, 2026)
Introduction: Humanisation of care in intensive care units (ICUs) has emerged as a crucial dimension of patient-centred medicine, addressing the psychological, emotional, and relational needs of critically ill patients and their families. Traditional ICU care often prioritises physiological stabilisation, but recent research highlights the importance of dignity, effective communication, and family involvement to improve overall outcomes. Objective: This systematic review aims to analyse international studies on interventions that promote humanised care in ICUs, focusing on communication, family engagement, psychological support, and innovative technologies to enhance patient and family experiences. Material and Methods: A systematic search was conducted targeting original international studies investigating humanisation strategies in ICU settings. Nine studies were selected based on relevance, methodological quality, and alignment with the PICO framework: ICU patients (P), humanisation interventions (I), standard ICU care (C), and psychological, cognitive, or relational outcomes (O). Nine articles published between 2005 and 2024 were included for analysis. Results and Discussion: Interventions such as structured communication protocols, family diaries, virtual reality for cognitive and emotional support, and discharge education programmes were found to enhance communication, family satisfaction, and psychological well-being. However, effects on anxiety and depression varied. Barriers to consistent implementation included staffing shortages and organisational culture. The integration of technologies such as virtual reality showed promising potential but requires larger-scale validation. Conclusions: Humanising ICU care enriches the critical care experience by fostering dignity, empathy, and collaboration among patients, families, and healthcare teams. While challenges remain, embedding these principles into ICU culture and practice can enhance recovery and resilience, highlighting the need for ongoing research and systemic commitment to compassionate critical care. Keywords Humanisation, intensive care unit, patient centered care, family centered care.